Sodium–Glucose Cotransporter 2 Inhibitors as Potential Antioxidant Therapeutic Agents in Cardiovascular and Renal Diseases - Tapan A. Patel; Hong Zheng; Kaushik P. Patel (Antioxidants)
Redox (reduction–oxidation) imbalance is a physiological feature regulated by a well-maintained equilibrium between reactive oxygen species (ROS) and oxidative stress (OS), the defense system of the body (antioxidant enzymes). The redox system comprises regulated levels of ROS in the cells, tissues and the overall organ system. The levels of ROS are synchronized by gradients of electrons that are generated due to sequential reduction and oxidation of various biomolecules by various enzymes. Such redox reactions are present in each cell, irrespective of any tissue or organ. Failure in such coordinated regulation of redox reactions leads to the production of excessive ROS and free radicals. Excessively produced free radicals and oxidative stress affect various cellular and molecular processes required for cell survival and growth, leading to pathophysiological conditions and, ultimately, organ failure. Overproduction of free radicals and oxidative stress are the key factors involved in the onset and progression of pathophysiological conditions associated with various cardiovascular and renal diseases. Sodium–glucose cotransporter 2 inhibitors (SGLT2is) are glucose-lowering drugs prescribed to diabetic patients. Interestingly, apart from their glucose-lowering effect, these drugs exhibit beneficial effects in non-diabetic patients suffering from various cardiovascular and chronic kidney diseases, perhaps due to their antioxidant properties. Recently, it has been demonstrated that SGLT2is exhibit strong antioxidant properties by reducing ROS and OS. Hence, in this review, we aim to present the novel antioxidant role of SGLT2is and their consequent beneficial effects in various cardiovascular and renal disease states.